1997
DOI: 10.1039/a608128b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of molybdenum-based catalysts using a radioisotope tracer method Part 1.—Hydrodesulfurization activity and structure of sulfided molybdena–alumina catalysts

Abstract: Hydrodesulfurization of radioactive 35S-labelled dibenzothiophene was carried out over a series of sulÐded molybdenaÈalumina catalysts containing 6È20 wt.% molybdena at temperatures in the range 280È380 ¡C and at a pressure of 50 kg cm~2. The sulfur exchange data and hydrodesulfurization activity were simultaneously obtained and the e †ect of molybdenum content on the structure of sulÐded catalysts was estimated. The sulfur exchange rates were approximately the same for all samples at the same temperature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
1
25
1
Order By: Relevance
“…ous Mo contents were calculated from the Arrhenius plots (lnkHDS as a function of 1/T; not shown here). The activation energy for HDS of DBT over the Mo/ TiO2 catalysts was almost constant at 92±8 kJ/mol, irrespective of the Mo loading, which is close to the 84 ±8 kJ/mol generally observed for Mo/Al2O3 cata lysts 44) . For the same Mo loading, the activities ob served over the high SSA titania were more than twice higher than those observed over the 256 m 2 ・g -1 alumina.…”
Section: Hds Activities and Sulfur Mobility Of Momentioning
confidence: 52%
See 3 more Smart Citations
“…ous Mo contents were calculated from the Arrhenius plots (lnkHDS as a function of 1/T; not shown here). The activation energy for HDS of DBT over the Mo/ TiO2 catalysts was almost constant at 92±8 kJ/mol, irrespective of the Mo loading, which is close to the 84 ±8 kJ/mol generally observed for Mo/Al2O3 cata lysts 44) . For the same Mo loading, the activities ob served over the high SSA titania were more than twice higher than those observed over the 256 m 2 ・g -1 alumina.…”
Section: Hds Activities and Sulfur Mobility Of Momentioning
confidence: 52%
“…The activities of Mo/Al2O3 catalysts described in a previous study are also shown in Fig. 8 44) . The value of kHDS for the Mo/TiO2 catalysts increased linearly with increasing Mo content up to about 16 wt% MoO3, and then decreased with further increasing Mo content (i.e.…”
Section: Hds Activities and Sulfur Mobility Of Momentioning
confidence: 82%
See 2 more Smart Citations
“…The results are shown in Fig. 1, together with the activities of Mo/Al2O3 catalysts described in a previous study 29) . The value of kHDS for the Mo/TiO2 catalysts increased linearly with increasing Mo content up to about 16 wt% MoO3 and then decreased with further increasing Mo content (i.e.…”
Section: Hds Activities Of Mo Catalysts Supported Onmentioning
confidence: 89%